Outcomes of Hemospray therapy in the treatment of intraprocedural upper gastrointestinal bleeding post‐endoscopic therapy. Issue 10 (12th January 2020) - Hussein, Mohamed; Alzoubaidi, Durayd; de la Serna, Alvaro; Weaver, Michael; Fernandez‐Sordo, Jacobo O; Rey, Johannes W; Hayee, Bu'Hussain; Despott, Edward; Murino, Alberto; Moreea, Sulleman; Boger, Phil; Dunn, Jason; et al.
Abstract : Introduction: With increasing advances in minimally invasive endoscopic therapies and endoscopic resection techniques for luminal disease, there is an increased risk of post‐procedure bleeding. This can contribute to significant burden on patient's quality of life and health resources when reintervention is required. Hemospray (Cook Medical, North Carolina, USA) is a novel haemostatic powder licensed for gastrointestinal bleeding. The aim of this single‐arm, prospective, non‐randomised multicentre international study is to look at outcomes in patients with upper gastrointestinal bleeds following elective endoscopic therapy treated with Hemospray to achieve haemostasis. Methods: Data was prospectively collected on the use of Hemospray from 16 centres (January 2016–November 2019). Hemospray was used during the presence of progressive intraprocedural bleeding post‐endoscopic therapy as a monotherapy, dual therapy with standard haemostatic techniques or rescue therapy once standard methods had failed. Haemostasis was defined as the cessation of bleeding within 5 min of the application of Hemospray. Re‐bleeding was defined as a sustained drop in haemoglobin (>2 g/l), haematemesis or melaena with haemodynamic instability after the index endoscopy. Results: A total of 73 patients were analysed with bleeding post‐endoscopic therapy. The median Blatchford score at baseline was five (interquartile range 0–9). The median Rockall score was six (interquartile range 5–7). Immediate haemostasis following the application of Hemospray was achieved in 73/73 (100%) of patients. Two out of 57 (4%) had a re‐bleed post‐Hemospray, one was following oesophageal endoscopic mucosal resection and the other post‐duodenal endoscopic mucosal resection. Both patients had a repeat endoscopy and therapy within 24 h. Re‐bleeding data was missing for 16 patients, and mortality data was missing for 14 patients. There were no adverse events recorded in association with the use of Hemospray. Conclusion: Hemospray is safe and effective in achieving immediate haemostasis following uncontrolled and progressive intraprocedural blood loss post‐endoscopic therapy, with a low re‐bleed rate.